Teleworking and Travel Purposes: UK Evidence after the COVID-19 Pandemic - Ignacio Belloc; José Ignacio Gimenez-Nadal; José Alberto Molina (Institute of Labor Economics (IZA), 2024)
Telework has gained increasing popularity in recent years, particularly following the COVID-19 pandemic, and is often considered a work practice that contributes to environmental sustainability by reducing commuting trips. However, the existing literature presents mixed findings regarding its potential effects on other types of travel, such as leisure and personal care trips. This paper examines the relationship between telework and daily travel time, utilizing data from the 2023 Extended Light Diary Digital Instrument (ELiDDI) survey, a nationally representative time use survey conducted in the UK in March 2023. Our findings indicate that teleworkers spend fewer minutes (e.g., 61 minutes) traveling per day compared to those working away from home, a result that remains robust even after excluding daily commuting time, suggesting that telework may lead to significant daily travel time savings. Further exploration reveals that telework is primarily related to reduced travel time for personal and housework-related activities, particularly among male teleworkers. These findings suggest that promoting telework policies could be an effective strategy not only for reducing commuting trips but also for achieving broader reductions in daily travel time, which may contribute to sustainability goals in the transportation sector and alleviate transportation-related environmental impacts.
Keywords: J21; J22; R41; 330; daily travel time; travel purposes; telework; time use; ELiDDI data; COVID-19